THE ROLE OF PRIMARY CARE IN PROMOTING A HEALTHY LIFESTYLE - Sokhiba Israilova Buribaevna (Web of Journals Publishing, 2024)
Primary health care is the foundation for building and maintaining the overall well-being of people. Primary care providers play an important role not only in the treatment of diseases, but also in the promotion and prevention of a healthy lifestyle. With a focus on education, early intervention, and personalized care, primary care serves as the primary advocate for health and well-being. This article provides information on the role of primary care in promoting healthy lifestyles.
Keywords: healthy lifestyle, primary care, healthy diet, health care, examination, hypertension.